2016
DOI: 10.1159/000446962
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Prokaryotic Expression and Purification of Human Interferon Alpha-2b Using a Maltose-Binding Protein Tag

Abstract: Human interferon alpha-2b (IFNα-2b) has therapeutic applications as an antiviral and antiproliferative drug and has been used for a wide range of indications. Efficient production of IFNα-2b in Escherichia coli has been difficult because the protein tends to form inclusion bodies. This obstacle has garnered interest in efficiently expressing IFNα-2b and overcoming its poor solubility. In this study, seven N-terminal fusion partners - hexahistidine (His6), thioredoxin, glutathione S-transferase (GST), maltose-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…After induction conditions optimized, the solubility of mu-IFN-CSP was up to 98.4%. The most optimal condition was at OD 600 = 0.9, inducing the culture at 34 °C for 6 h with 0.1 mM IPTG, which is consistent with previous reports that low temperature and low IPTG concentration may improve the solubility of target protein (Vu et al 2016 ; Xu et al 2006 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…After induction conditions optimized, the solubility of mu-IFN-CSP was up to 98.4%. The most optimal condition was at OD 600 = 0.9, inducing the culture at 34 °C for 6 h with 0.1 mM IPTG, which is consistent with previous reports that low temperature and low IPTG concentration may improve the solubility of target protein (Vu et al 2016 ; Xu et al 2006 ).…”
Section: Discussionsupporting
confidence: 88%
“…Most of them have reported that the IFNs are expressed as inclusion bodies in recombinant E. coli (Neves et al 2004 ; Srivastava et al 2005 ; Valente et al 2004 ). The refolding of misfolding and aggregation IFNs from inclusion bodies usually need extensive optimization, which makes the refolding procedures cumbersome (Middelberg 2002 ; Vu et al 2016 ). Up to now, it is still hard to produce soluble IFNs in recombinant E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, one of eight tags – His6, Sumo, Trx, GST, PDIb′a′, MBP, NusA, or PDI – was attached to the N terminus of hFGF21, resulting in eight recombinant vectors. Previously, these tags have been used in multiple studies to improve the soluble expression of various recombinant proteins in E. coli 19 23 , 27 , 28 . In the present study, the hFGF21 fusion vectors were transformed into the E. coli BL21(DE3) to characterise the behaviour of the fusion proteins expressed in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…N utilization substance protein A (NusA) is one of the most commonly used protein tagging labels for enhancing the yield and solubility of recombinant proteins (Cabrita et al, 2006;Vu et al, 2016;Sun et al, 2012). A fusion-tag efficiency evaluating assay indicated that seven out of eight tested large molecular proteins had been efficiently expressed at high solubility by NusA-tag, while only four were expressed with other tags such as thioredoxin (TRX), small ubiquitin-like modifier (SUMO), maltose-binding protein (MBP), glutathione S-transferase (GST) etc.…”
Section: Introductionmentioning
confidence: 99%